Study of changes in the pulsation period of 148 Galactic Cepheid variables. Issue 2 (24th January 2022) - Csörnyei, G; Szabados, L; Molnár, L; Cseh, B; Egei, N; Kalup, Cs; Kecskeméthy, V; Könyves-Tóth, R; Sárneczky, K; Szakáts, R
ABSTRACT: Investigating period changes of classical Cepheids through the framework of O − C diagrams provides a unique insight to the evolution and nature of these variable stars. In this work, the new or extended O − C diagrams for 148 Galactic classical Cepheids are presented. By correlating the calculated period change rates with the Gaia EDR3 colours, we obtain observational indications for the non-negligible dependence of the period change rate on the horizontal position within the instability strip. We find period fluctuations in 59 Cepheids with a confidence level of 99 per cent, which are distributed uniformly over the inspected period range. Correlating the fluctuation amplitude with the pulsation period yields a clear dependence, similar to the one valid for longer period pulsating variable stars. The non-negligible amount of Cepheids showing changes in their O − C diagrams that are not or not only of evolutionary origin points towards the need for further studies for the complete understanding of these effects. One such peculiar behaviour is the large amplitude period fluctuation in short period Cepheids, which occurs in a significant fraction of the investigated stars. The period dependence of the fluctuation strength and its minimum at the bump Cepheid region suggests a stability enhancing mechanism for this period range, which agrees with current pulsation models.